Answer:
11) 6x^2+ 6x^3 = 6.x.x+6.x.x.x
12) -6x^2 + (-6) x^3 = -6.x.x + (-6).x.x.x
13) 5x - 8x = 5.x -8.x
Explanation:
Let us solve the question one by one.
11) 6x^2+ 6x^3
In order to convert the polynomial in the factored form, we see which factors are common in all terms in the polynomial.
![6x^2 = 6.x.x\\6x^3 =6.x.x.x](https://img.qammunity.org/2022/formulas/mathematics/high-school/6js5fw53keoqletp5o7nobbqvsmvbuyk3e.png)
The factored form is:
![= 6.x.x+6.x.x.x](https://img.qammunity.org/2022/formulas/mathematics/high-school/eqr6c1yr9a00450apv9rrdg0fl8oehz06x.png)
12) -6x^2 + (-6) x^3
Similarly, as 11
![-6x 2 =-6.x.x\\-6x^3=-6.x.x.x](https://img.qammunity.org/2022/formulas/mathematics/high-school/mg2v65ejizukujeopjap8z9fc2unwle4l6.png)
The factored form is:
![=-6.x.x+ (-6).x.x.x](https://img.qammunity.org/2022/formulas/mathematics/high-school/vjc7lktjyms6ywz89y1ofp9uko2xly9cez.png)
13) 5x - 8x
We can clearly see that there is only one common factor in both terms which is x
![5x = 5.x\\8x = 8.x](https://img.qammunity.org/2022/formulas/mathematics/high-school/j5pf77kj6v4pryugglznu95xvtbl2zzefp.png)
The factored form is:
![=5.x-8.x](https://img.qammunity.org/2022/formulas/mathematics/high-school/812f960jpmuw3nsffcklhc1r7lgor4d5a5.png)
Hence,
11) 6x^2+ 6x^3 = 6.x.x+6.x.x.x
12) -6x^2 + (-6) x^3 = -6.x.x + (-6).x.x.x
13) 5x - 8x = 5.x -8.x